Environmental Landscape Design Based on Artificial Intelligence and Digital Space Technology - Weina Wang (Journal of Electrical and Computer Engineering)
In order to improve the effect of future environmental landscape design, this study combines artificial intelligence technology and digital space technology to construct an environmental landscape design system. Moreover, this study uses polygons to model external landscape plants instead of modeling the microelement structure of landscape plants and re-polygonize them, which simplifies the model structure of landscape plants and improves computational efficiency. In addition, this study conducts collision detection in the growth of landscape plants to make it more realistic and more efficient and studies and analyzes the digital construction of landscape plants. Finally, after constructing an intelligent system, the effect of the system in this study is verified. Through data analysis, it can be seen that the environmental landscape design system based on artificial intelligence and digital space technology proposed in this study has good digital space structure expression effect and design effect.